Insight into the corrosion evolution of Fe-based amorphous coatings under wet-dry cyclic conditions. (1st October 2019) - Wu, J.; Cui, J.P.; Zheng, Q.J.; Zhang, S.D.; Sun, W.H.; Yang, B.J.; Wang, J.Q.
Abstract: Understanding the corrosion behavior of Fe-based amorphous coatings under wet-dry cyclic conditions is of pretty importance for coating applications in marine environments. In this paper, the corrosion evolutions of the coatings under wet-dry cyclic conditions were investigated by electrochemical impedance spectroscopy (EIS), scanning electron microscope (SEM) and transmission electron microscopy (TEM). Accurate charge transfer resistance ( R t ) was obtained through fitting EIS results using a modified transmission line equivalent circuit model and a landscape map of R t was constructed for a panoramic investigation on coating corrosion. The results show that the corrosion rate of the coating changes cyclically under wet-dry cyclic conditions. Corrosion within a single wet-dry cycle can be presented as four stages: an initial decrease of corrosion rate due to passivation or repassivation when the coating is wetted, then a slow increase due to concentrated aggressive ions with solution evaporation, followed by a rapid increment associated with fast oxygen transport under ultrathin solution film and finally a stable stage as solution dries out. It is deduced that an oxygen concentration gradient can form between the inside and the outside of coating pores when the solution film over the coating is very thin, which further promotes the localized corrosion in the pores. According to the landscape map of R t, the coating maintains its high corrosion resistance for the initial 33 wet-dry cycles. But its corrosion resistance decreases significantly in the 35th wet-dry cycle accompanied by the attack of localized corrosion. After 65 wet dry cycles, the coating fails due to the penetration of localized corrosion. The interparticle oxide layers are defective, which enhances the localized corrosion process. Graphical abstract: Image 1064 Highlights: Accurate charge transfer resistance has been obtained for wet-dry corrosion of coatings. Corrosion rate of coatings changes cyclically under wet-dry cyclic conditions. Oxygen concentration gradient under thin solution film promotes localized corrosion in pores.